Phacoemulsification with posterior chamber intraocular lens versus extracapsular cataract extraction (ECCE) with posterior chamber intraocular lens for age-related cataract. - Silva, d; Riaz, Y; Evans, JR (2014)
BACKGROUND: Age-related cataract is one of the leading causes of blindness worldwide. Therefore, it is important to establish the most effective surgical technique for cataract surgery. OBJECTIVES: The aim of this review is to examine the effects of two types of cataract surgery for age-related cataract: phacoemulsification and extracapsular cataract extraction (ECCE). SEARCH METHODS: We searched CENTRAL (which contains the Cochrane Eyes and Vision Group Trials Register) (The Cochrane Library 2013, Issue 4), Ovid MEDLINE, Ovid MEDLINE In-Process and Other Non-Indexed Citations, Ovid MEDLINE Daily, Ovid OLDMEDLINE (January 1946 to May 2013), EMBASE (January 1980 to May 2013), Latin American and Caribbean Literature on Health Sciences (LILACS) (January 1982 to May 2013), Web of Science Conference Proceedings Citation Index - Science (CPCI-S) (January 1970 to May 2013), the metaRegister of Controlled Trials (mRCT) (www.controlled-trials.com), ClinicalTrials.gov (www.clinicaltrials.gov) and the WHO International Clinical Trials Registry Platform (ICTRP) (www.who.int/ictrp/search/en). We did not use any date or language restrictions in the electronic searches for trials. We last searched the electronic databases on 13 May 2013. SELECTION CRITERIA: We included randomised controlled trials of phacoemulsification compared to ECCE for age-related cataract. DATA COLLECTION AND ANALYSIS: Two authors independently selected and assessed all studies. We defined two primary outcomes: 'good functional vision' (presenting visual acuity of 6/12 or better) and 'poor visual outcome' (best corrected visual acuity of less than 6/60) at three and 12 months after surgery. We also collected data on intra and postoperative complications, and the cost of the procedures. MAIN RESULTS: We included 11 trials in this review with a total of 1228 participants, ranging from age 45 to 94. The studies were generally at unclear risk of bias due to poorly reported trial methods. No study reported presenting visual acuity, so we report both uncorrected (UCVA) and best corrected visual acuity (BCVA). Studies varied in visual acuity assessment methods and time frames at which outcomes were reported. Participants in the phacoemulsification group were more likely to achieve UCVA of 6/12 or more at three months (risk ratio (RR) 1.81, 95% confidence interval (CI) 1.36 to 2.41, two studies, 492 participants) and one year (RR 1.99, 95% CI 1.45 to 2.73, one study, 439 participants). People in the phacoemulsification group were also more likely to achieve BCVA of 6/12 or more at three months (RR 1.12, 95% CI 1.03 to 1.22, four studies, 645 participants) and one year (RR 1.06, 95% CI 0.99 to 1.14, one study, 439 participants), but the difference between the two groups was smaller. No trials reported BCVA less than 6/60 but three trials reported BCVA worse than 6/9 and 6/18: there were fewer events of this outcome in the phacoemulsification group than the ECCE group at both the three-month (RR 0.33, 95% CI 0.20 to 0.55, three studies, 604 participants) and 12-month time points (RR 0.62, 95% CI 0.36 to 1.05, one study, 439 participants). Three trials reported posterior capsule rupture: this occurred more commonly in the ECCE group than the phacoemulsification group but small numbers of events mean the true effect is uncertain (Peto odds ratio (OR) 0.56, 95% CI 0.26 to 1.22, three studies, 688 participants). Iris prolapse, cystoid macular oedema and posterior capsular opacification were also higher in the ECCE group than the phacoemulsification group. Phacoemulsification surgical costs were higher than ECCE in two studies. A third study reported similar costs for phacoemulsification and ECCE up to six weeks postoperatively, but following this time point ECCE incurred additional costs due to additional visits, spectacles and laser treatment to achieve a similar outcome. AUTHORS' CONCLUSIONS: Removing cataract by phacoemulsification may result in a better visual acuity compared to ECCE, with a lower complication rate. The review is currently underpowered to detect differences for rarer outcomes, including poor visual outcome. The lower cost of ECCE may justify its use in a patient population where high-volume surgery is a priority, however, there are a lack of data comparing phacoemulsification and ECCE in lower-income settings.